Improving Patient Knowledge and Safe Use of Opioids: A Randomized Controlled Trial. (2nd March 2015) - McCarthy, Danielle M.; Wolf, Michael S.; McConnell, Ryan; Sears, Jill; Chevrier, Allison; Ahlstrom, Eric; Engel, Kirsten G.; Cameron, Kenzie A.; Adams, James G.; Mark Courtney, D.; Bird, Steven
Abstract Objectives The use of opioid analgesics in the United States has significantly increased in recent years. However, there is minimal consensus on what discharge counseling should accompany these high‐risk prescriptions and large variations in what is done in practice. The objective of this study was to evaluate the effect of a dual‐modality (written and spoken) literacy‐appropriate educational strategy on patients' knowledge of and safe use of opioid analgesics. Methods This was a prospective, randomized controlled trial. Consecutive discharged patients at an urban academic ED (>88, 000 visits) with new prescriptions for hydrocodone‐acetaminophen were enrolled. Patients were randomized to receive either usual care or the educational intervention. The educational intervention was a one‐page information sheet about hydrocodone‐acetaminophen, which was both given to the patients and read aloud by the research assistant (nonblinded). Follow‐up phone calls were conducted 4 to 7 days after the visit to assess patient knowledge about the medication and self‐report of activities associated with safety of use (e.g., double‐dipping with acetaminophen, storage, use with alcohol or while driving). Results A total of 274 patients were enrolled; 210 completed follow‐up (110 usual care and 100 intervention). No significant differences in baseline characteristics emerged between the study arms; 42% were male, and 51% were white, with a median age of 43 years. Half of patients had non–back pain orthopedic injuries (49.5%). On follow‐up, overall knowledge was poor, with only 28% able to name both active ingredients in the medication. The intervention group had better knowledge of precautions related to taking additional acetaminophen (usual care 18.2%, 95% confidence interval [CI] = 10.9% to 25.5% vs. intervention 38%, 95% CI = 28.3% to 47.7%; difference = 27.6, 95% CI of difference = 21.5 to 33.7) and knowledge of side effects (usual care median = 1, interquartile range [IQR] 0 to 2 vs. intervention median = 2, IQR = 1 to 2; p < 0.0001). Additionally, those who received the intervention were less likely to have reported driving within 6 hours after taking hydrocodone (usual care 13.6%, 95% CI = 7.2% to 20% vs. intervention 3%, 95% CI = –0.3% to 6.3%; difference = 10.6, 95% CI of difference = 3.4 to 17.9). There was no difference between groups related to knowledge about drinking alcohol while taking hydrocodone (overall 18.1%) or knowledge that the opioid could be addictive (overall 72.4%). Conclusions This simple strategy improved several, but not all, aspects of patient knowledge and resulted in fewer patients in the intervention arm driving while taking hydrocodone. Integration of a patient education document into conversations about opioids holds promise for improving patient knowledge about these high‐risk medications.